2003
DOI: 10.1152/ajpcell.00287.2002
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species are important mediators of taurine release from skeletal muscle cells

Abstract: The present study illustrates elements of the signal cascades involved in the activation of taurine efflux pathways in myotubes derived from skeletal muscle cells. Exposing primary skeletal muscle cells, loaded with 14C-taurine, to 1) hypotonic media, 2) the phospholipase A2 (PLA2) activator melittin, 3) anoxia, or 4) lysophosphatidyl choline (LPC) causes an increase in 14C-taurine release and a concomitant production of reactive oxygen species (ROS). The antioxidants butulated hydroxy toluene and vitamin E in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 44 publications
2
76
0
1
Order By: Relevance
“…[26][27][28] Similarly, taurine is known to play important roles against reactive oxygen species and hypoxia in several organs, including the those of the CNS and the vasculature. [29][30][31][32][33] Both intermittent hypoxia and increased oxidative stress are hallmark characteristics of OSA, 34 and the degree of oxidative stress associated with OSA has emerged as an important determinant of cognitive dysfunction in both animal models and in children. [35][36][37] A unique and intriguing observation in the present study involves the differential and predictable changes in urinary neurotransmitters in children with OSA and without evidence of neurocognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Similarly, taurine is known to play important roles against reactive oxygen species and hypoxia in several organs, including the those of the CNS and the vasculature. [29][30][31][32][33] Both intermittent hypoxia and increased oxidative stress are hallmark characteristics of OSA, 34 and the degree of oxidative stress associated with OSA has emerged as an important determinant of cognitive dysfunction in both animal models and in children. [35][36][37] A unique and intriguing observation in the present study involves the differential and predictable changes in urinary neurotransmitters in children with OSA and without evidence of neurocognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…ROS production increases within the first minutes following hypotonic exposure in, e.g., NIH3T3 fibroblasts (492), skeletal muscle (753), and hepatocytes (1031). The swellinginduced ROS production in HTC cells is reduced in the presence of the NADPH oxidase inhibitor diphenyl iodonium (DPI).…”
Section: Effect Of Cell Volume Perturbations On Cellular Ros Productionmentioning
confidence: 99%
“…Ørtenblad et al 77) used excised muscle tissue and labeled taurine ( 14 C-taurine) to prove that contracting muscles release taurine upon stimulation with melittin, a toxin that facilitates production of reactive oxygen species via activation of phospholipase A2, or upon anoxic stimulation. Inhibition of taurine release by antioxidants such as vitamin E was also confirmed.…”
Section: Taurinementioning
confidence: 99%
“…Inhibition of taurine release by antioxidants such as vitamin E was also confirmed. Considering the anoxic conditions of muscles and increased oxidative stress during exercise, it can be said that the study by Ørtenblad et al 77) revealed a part of the mechanism underlying exercise-induced taurine release from muscles into the bloodstream.…”
Section: Taurinementioning
confidence: 99%